Clinical and Economic Outcomes of Patients with Osteoporosis Undergoing Spine Fusion Surgery in Japan - Kotaro Nishida; HyeJin Park; Mami Ogiri; Anne Rossi (Spine Surgery and Related Research, 2024)
Introduction: Spinal fusion surgery with instrumentation is a treatment of choice for many spinal disorders; however, there is little data related to factors associated with early and late outcomes, especially among patients with poor bone quality (e.g., osteoporosis). We conducted this study to characterize the epidemiology and outcomes of patients undergoing spinal fusion surgery with instrumentation in Japan, especially in patients with poor bone quality and those needing additional fixation methods. Methods: This retrospective observational study used real-world health insurance claims data from the Japanese Medical Data Vision. Adult patients undergoing an index spinal fusion procedure from April 1, 2010, to September 30, 2017, with procedural details, length of stay (LOS), total in-hospital costs, spine-related reoperation, all-cause readmission, and postoperative complications recorded. Data were summarized descriptively overall, by osteoporosis status, and additional fixation method used, and were analyzed in bivariate analyses. Multivariate logistic and linear regressions were used to explore associations between covariates and variables of interest. Results: A total of 22,932 patients (mean age, 67.3 years; 51.2% male) met the study criteria and were included. A total of 5,288 (23.0%) patients had osteoporosis, and 2,507 (10.9%) needed additional fixation methods; these patients were older, more frequently female, and had higher Elixhauser comorbidity index scores. Osteoporosis and additional fixation use were also associated with longer LOS, higher hospital costs, and higher rates of complications. Conclusions: Patients with osteoporosis and those needing additional fixation methods have a higher risk for procedural and postoperative complications, reoperation, longer LOS, and higher total hospital costs.